2021
DOI: 10.47068/ctns.2020.v9i20.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maturity Stages on Potential Nutritive Value of Vicia Cracca (L.) Hay

Abstract: The aim of the current experiment was to determine the effect of harvesting stage on the potential nutritive value. Vicia cracca plant was harvested at three maturity stages (before flowering, flowering and seeding). Vicia cracca plants were dried at 70 °C and grinded in a hand-mill with 1 mm sieve for chemical analysis. Crude protein, crude oil, crude ash, condensed tannin, acid detergent fiber (ADF), and neutral detergent fiber (NDF) parameters were investigated as the chemical composition. Harvesting stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Vicia cracca had consistently high aNDFom concentrations across all cuts, demonstrating a minimal impact of maturity stage on the species' aNDFom content (Figure 12B). The aNDFom concentrations observed in this study are comparable with values reported in other studies (Ciftci et al, 2021;Gürsoy, 2021). Vicia sepium, however, had low aNDFom concentrations in each harvest, further demonstrating its promising nutritive value.…”
Section: Agronomic Potential Of Selected Native Legumes (Paper Iv)supporting
confidence: 89%
“…Vicia cracca had consistently high aNDFom concentrations across all cuts, demonstrating a minimal impact of maturity stage on the species' aNDFom content (Figure 12B). The aNDFom concentrations observed in this study are comparable with values reported in other studies (Ciftci et al, 2021;Gürsoy, 2021). Vicia sepium, however, had low aNDFom concentrations in each harvest, further demonstrating its promising nutritive value.…”
Section: Agronomic Potential Of Selected Native Legumes (Paper Iv)supporting
confidence: 89%